10 years of flood events, study of the adaptation capacity of the people living in the Riparian Area of the Madiun River. Issue 1 (May 2020) - Wahyudi, A; Ritohardoyo, S; Sunarto,; Pitoyo, A J
Abstract: The flood disaster is a severe threat to households living in the riparian area of the Madiun River. The flood proved the threat in Madiun River in 2007. For more than 10 (ten) years they remained in settlements in the riparian area of the Madiun River, this situation caused them to adapt to their environmental conditions. The purpose of this study was to determine the characteristics of the community, measure the level of knowledge of floods, find out public perceptions, the adaptive capacity of the household occupants of the riparian area of the Madiun River and the local wisdom of the community when facing the threat of floods. Retrieval of data using a questionnaire that was addressed to 100 respondents in the riparian area population randomly selected. The results showed that the knowledge level (94%) and perception (90%) of the public against high floods. The capacity of community adaptation to flood hazards consists of 89% low, 10% moderate, and only 1% which has a high level of adaptation. The local wisdom of the residents of the riparian area with a flood-prone environment consists of wisdom in aspects of value, aspects of a building structure, and aspects of local intelligence in recognizing signs of flooding.